THE COMPARISON USING EXPECTATION-MAXIMIZATION ALGORITHM AND C4.5 ALGORITHM TO PREDICT THE RESULT OF BIOGAS PRODUCTION AS A POWER PLANT AT PT BUDI STARCH & SWEETENER (BSSW) - Eriska Vivian Astuti eriska; Nurmayanti Nurmayanti; Rima Mawarni; Asep Afandi; Aris Munandar (IJISCS (International Journal of Information System and Computer Science), 2022)
Biogas is the result of the development of alternative energy that has formed through the decomposition of organic matter through an anaerobic fermentation process (without oxygen) that produces gas in the form of methane gas (CH4) which has burned. Biogas is a kind of renewable energy because it has a high methane content and calorific value. Methane has one carbon in each chain, which can produce combustion that is more environmentally friendly when compared to fuels that have long carbon chains using specific calculation techniques or methods, a data mining process has been carried out to locate interesting patterns or information in selected data to manipulate the data into more valuable information by extracting significant patterns from the database.